2019
DOI: 10.1016/j.neuron.2019.08.014
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Nanoscale Calcium Channel and Synaptic Vesicle Topographies Contribute to the Diversity of Synaptic Function

Abstract: Highlights d Number of presynaptic calcium channels (Ca V ) does not correlate with synaptic strength d Weak synapses are more sensitive to competition with exogenous Ca 2+ chelators d EM immunogold labeling of Ca V 2.1 and Munc13-1 shows synapse-specific nanotopographies d Different nanoscale Ca V -synaptic vesicle arrangements explain functional differences

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 99 publications
(168 reference statements)
7
138
0
Order By: Relevance
“…This is contrary to what the isoform-specific CDF, as characterized in non-neuronal cells, would have predicted (Chaudhuri et al, 2004;Weyrer et al, 2019); it likely reflects instead a differential spatial relationship of the two isoforms to fuse-competent synaptic vesicles, with a tight and loose coupling configuration for Ca V 2.1[EFa] and Ca V 2.1[EFb], respectively (Figure 2Cc; Thalhammer et al, 2017). More in general, AS of Ca V 2.1 might underlie most of the intra-and inter-synaptic differences in nanoscale topographical arrangements of this channel, as recently revealed (Holderith et al, 2012;Nakamura et al, 2015;Rebola et al, 2019).…”
Section: Alternative Splicing Of P/q-type Ca 2+ Channels In Presynaptmentioning
confidence: 78%
“…This is contrary to what the isoform-specific CDF, as characterized in non-neuronal cells, would have predicted (Chaudhuri et al, 2004;Weyrer et al, 2019); it likely reflects instead a differential spatial relationship of the two isoforms to fuse-competent synaptic vesicles, with a tight and loose coupling configuration for Ca V 2.1[EFa] and Ca V 2.1[EFb], respectively (Figure 2Cc; Thalhammer et al, 2017). More in general, AS of Ca V 2.1 might underlie most of the intra-and inter-synaptic differences in nanoscale topographical arrangements of this channel, as recently revealed (Holderith et al, 2012;Nakamura et al, 2015;Rebola et al, 2019).…”
Section: Alternative Splicing Of P/q-type Ca 2+ Channels In Presynaptmentioning
confidence: 78%
“…We assessed whether Cav2.1 particles localize more closely to each other than expected by chance, and found that NNDs between real Cav2.1 particles are slightly, but significantly, smaller than those between simulated particles ( Figure 4 D). A few different models for the spatial relationship between Cav2.1 and release sites have been proposed [ 59 , 60 , 61 ]. In synapses displaying tight coupling between calcium influx and vesicle release sites a perimeter release model [ 59 , 60 ] and one-to-one correspondence of Cav2.1 clusters and vesicle release sites [ 61 ] have been proposed, while synapses with loose coupling were modeled by an exclusion zone model, with Cav2.1 being excluded from vesicle release sites but randomly distributed in the remaining synaptic area [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…RIM1α and RIM-BP2 form liquid condensates in vitro, and these condensates organize tethering of voltage-gated calcium channels 6,43 44 . In aggregate, it appears most likely that distinct liquid assemblies may exist within an active zone, one containing RIM1 and RIM-BP2 to tether calcium channels 3,6 , and a different phase with Liprin-α, RIM and Munc13-1.…”
Section: Interactions Of Presynaptic Liquid Phasesmentioning
confidence: 99%